SOCIAL ETHICS POLITICAL BUZZER IN THE LIVING RELIGIONS (Qur’an and Hadith) - Danarta, Agung (Jurnal Sosiologi Agama, 2022)
The article discusses the first three main issues, what is the purpose of the political buzzer in social media, and how it works. Second, the need for ethics in doing so becomes a Buzzer. Third, the ethical model of buzzing (dissemination of information) on social media according to the Qur’an and Hadith. The research method used is literature studies and is descriptive analytical. Primary data sources in the form of the Qur’an and hadith processed using the Maktabah Syamilah are traced with a theme that corresponds to the buzzer material. Data analysis using content analysis techniques. This research resulted in the conclusion that buzzer practices in digital platforms were adopted from the diffusion theory of innovation. This theory describes the process of how an innovation or idea is communicated through a particular channel continuously over time to a group of members of a social system. Content / messages created by buzzers are processed using simulacra theory. In simulacra theory, man does not exist in the presence of real reality, but always thinks imaginary and delusional in seeing reality. This situation makes truth and falsehood, reality and design have something in common and difficult to distinguish. This situation is what gives rise to the great destructive potential of buzzers to the order of society, so that buzzer activity on social media needs to be regulated by the rule of law derived from the ethics of the Quran and hadith. The ethics of the Qur’an and hadith stipulate that man has rights and obligations.